Epidemiological and socio-cultural study of burn patients in M. Y. Hospital, Indore, India - Jaiswal Ashish; Aggarwal Himanshu; Solanki Pooja; Lubana P; Mathur R; Odiya Sudarshan (Indian Journal of Plastic Surgery)
Background: Developing countries have a high incidence of burn injuries, creating a formidable public health problem. The exact number of cases is difficult to determine: however in a country like India, with a population of over 1 billion, we would estimate 700,000 to 800,000 burn admissions annually. Objective: The study was done to investigate the epidemiology of various causations and their outcomes in terms of morbidity and mortality. Also, the effect of social stigma and cultural issues associated with burns on the victim and his family was assessed. Materials and Methods: All burn cases (n=412) admitted to the burns unit of M. Y. Hospital, Indore over a period of one year (2005-2006) were investigated. The data regarding sex, age predisposition, geographical origin, mode and nature of injury were obtained by questionnaire-interview with the patient themselves. Clinical assessment was done in the form of depth and extent of injury and complications. In case of mortality, again various factors like age, sex and cause of death were analyzed. The data was analyzed by SPSS 11.0 version. The interrelationship between various factors was studied using multivariate logistic regression analysis. Results: Burns were found more commonly in middle-aged groups. The incidence was more in females as an absolute number (70.3%) as well as when stratified by age. Most burns were domestic, with cooking being the most prevalent activity. Flame (80.3%) was the most common agent. Most of the cases of burn were accidental (67.7%). Moreover, the patients had third degree burn that leads to more mortality in our circumstances. Death occurred in more than one-half (62.3%) of cases with septicaemia and disseminated intravascular coagulation (35.4%) as the leading causes. When using logistic regression analysis, the outcome of the burn injury was significantly associated with degree, depth, extent and mode of injury. Conclusion: This series provides an overview of the most important aspects of burn injuries for hospital and non-hospital healthcare workers. The majority of deep burns are accidental, seen in middle-aged housewives as a result of flame burns, and lead to death. So measures should be taken to provide proper education to prevent these accidents and ensure safety.